Analisis Perkembangan pada Anak Speech Delay di Paud X - Juwariantini; Manispal (UNISBA Press, 2021)
Abstract. Seeing the development of Speech Delay children in PAUD, the parents have not realized that following the child's development is the most important thing for their child to speak with correct grammar. When speaking, they do not pay attention to the grammar spoken, not to involve the child speaking in every situation by correcting the child's pronunciation that is still wrong. The use of technology media that does not support children's vocabulary. Consultations have not been routine to find out the child's development to doctors and child psychologists. The research is a case study qualitative research, the subject of this research is a child who experiences Speech Delay in PAUD in one of the children with data collection techniques through interviews and observation studies. The results showed an increase in developmental abilities in children who experienced Speech Delay from the results of interviews with parents. Parents realize that following their child's development is the most important thing for their child to speak grammatically correct. When speaking always pay attention to the grammar spoken, Always involve the child speaking in every situation by correcting the child's pronunciation that is still wrong. The use of technology media that supports children's vocabulary. Regular consultations to find out the child's development at the doctor and child psychologist. Planning, implementation and evaluation that the teacher has done is good, Prepares examples of a series of alphabets, Prepares recordings with cellphones, Sees research locations, Sees research objects, Prepares questions. Abstrak. Melihat adanya perkembangan pada anak Speech Delay di PAUD, yang Orang tua belum menyadari bahwa mengikuti perkembangan anak merupakan hal paling penting demi anak mereka untuk berbicara dengan tata bahasa yang benar. Saat berbicara belum memperhatikan tata bahasa yang diucapkan, belum melibatkan anak berbicara pada setiap keadaan dengan memperbaiki pengucapan anak yang masih keliru. Penggunaan media teknologi yang belum mendukung pembendaharaan kata anak-ana. Konsultasi belum rutin untuk mengetahui perkembangan anak pada Dokter dan Psikolog anak. Penelitian yang dilakukan adalah penelitian kualitatif studi kasus, subjek penelitian ini adalah anak yang mengalami Speech Delay di PAUD pada salah seorang anak teknik pengumpulan data melalui wawancara dan studi observasi. Hasil penelitian menunjukkan adanya peningkatan kemampuan perkembangan pada anak yang mengalami Speech Delay dari hasil wawancara dengan orang tua. Orang tua menyadari bahwa mengikuti perkembangan anak merupakan hal paling penting demi anak mereka untuk berbicara dengan tata bahasa yang benar. Saat berbicara selalu memperhatikan tata bahasa yang diucapkan, Selalu melibatkan anak berbicara pada setiap keadaan dengan memperbaiki pengucapan anak yang masih keliru. Penggunaan media teknologi yang mendukung pembendaharaan kata anak-anak. Konsultasi rutin untuk mengetahui perkembangan anak pada Dokter dan Psikolog anak. Perencanaan, pelaksaan dan evaluasi yang guru lakukan sudah baik, Mempersiapkan contoh-contoh serangkaian alphabet, Mempersiapkan rekaman dengan Handphone, Melihat lokasi penelitian, Melihat objek penelitian, Mempersiapkan pertanyaan-pertanyaan.